The Impact of Inadequate Governance on Security in Nigeria: The Approach of Police Force Command Abuja - Ajiteru Sherif Abdul Raheem; Sulaiman T.H; Abalaka J. N (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This study looked at the relationship between Nigeria's ongoing insecurity and poor governance. The article makes the theoretical case that the injustice, corruption, and self-serving leadership of Nigeria's leadership class are to blame for the country's current security problems. Ethnic, communal, religious, and resource-related conflicts have persisted throughout most of Nigeria since the country's restoration to democracy in 1999, following nearly three decades of military administration. This is made worse by the leadership's apparent inability to solve important national concerns like reducing poverty, creating jobs, allocating resources, developing infrastructure, etc. Accordingly, the study concludes that Although it is a huge task, combating insecurity in Nigeria is not insurmountable. Nigerians must therefore come together, and the ruling class must become fully committed to combating insecurity and forging a strong political will.